2021
DOI: 10.1542/peds.2020-0272
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use Among Latinx Children After 2017 Executive Actions on Immigration

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…3,4 In a study reported by the Urban Institute, researchers found that in 2019, 1 in 5 adults in immigrant families with children avoided public benefits and 31.5% did so in low-income families. 5 Although there was no chilling effect found in the use of services by insured Latino children in this study, Cholera et al 1 add to the many past and, likely, future studies that continue to reveal that policies of exclusion have negative impacts on the health of immigrant communities. 6,7 Cholera et al 1 remind us that such policies can further marginalize low-income undocumented immigrant communities and that the relationship between immigration status and health requires further investigation from a social determinants of health framework to truly appreciate inequities created by social structures, policies, and institutions.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…3,4 In a study reported by the Urban Institute, researchers found that in 2019, 1 in 5 adults in immigrant families with children avoided public benefits and 31.5% did so in low-income families. 5 Although there was no chilling effect found in the use of services by insured Latino children in this study, Cholera et al 1 add to the many past and, likely, future studies that continue to reveal that policies of exclusion have negative impacts on the health of immigrant communities. 6,7 Cholera et al 1 remind us that such policies can further marginalize low-income undocumented immigrant communities and that the relationship between immigration status and health requires further investigation from a social determinants of health framework to truly appreciate inequities created by social structures, policies, and institutions.…”
mentioning
confidence: 56%
“…5 Although there was no chilling effect found in the use of services by insured Latino children in this study, Cholera et al 1 add to the many past and, likely, future studies that continue to reveal that policies of exclusion have negative impacts on the health of immigrant communities. 6,7 Cholera et al 1 remind us that such policies can further marginalize low-income undocumented immigrant communities and that the relationship between immigration status and health requires further investigation from a social determinants of health framework to truly appreciate inequities created by social structures, policies, and institutions. 8 Furthermore, that the Latino community was chosen to explore immigration policy effects on health speaks to institutional racism driving immigration reform and enforcement.…”
mentioning
confidence: 56%
“…Across several studies, medical staff have also confirmed the decline of Latinx immigrant patients in health facilities compared to before the 2016 election [53][54][55], and one study found an increase in medical appointment cancellations for uninsured Latinx children after enaction of restrictive immigration policies by the Trump administration in early 2017 [56]. US-born children of undocumented immigrant mothers were also found to have a 17% higher rate of being uninsured compared to children with US-citizen mothers [57]. Although there are places where health services are provided to immigrants without lawful status, studies have shown that those localities are sometimes avoided due to a fear of presence of local police and ICE and fear of personal information being shared with ICE officers [10,58].…”
Section: Relationship Between Immigration Stress and Healthcare Utili...mentioning
confidence: 93%
“…Third, more attention is needed on the potential mechanisms that could explain the observed link between sociopolitical stress and adverse birth outcomes among Latina mothers, such as changes in the use of prenatal care. Existing literature finds that racist, anti-immigrant events can lead to "chilling effects," whereby feelings of fear, anxiety, and mistrust prevent immigrants from seeking needed healthcare services [31][32][33][34][35]. A recent study of patients in Houston, Texas found significant declines in prenatal care visits among expectant immigrant Latina mothers from Mexico and Central American following the launching of Trump's campaign in the summer of 2015 [21].…”
Section: Introductionmentioning
confidence: 99%